2023
DOI: 10.3390/nano13061105
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cauliflower-Patterned CuFe2O4 Electrode Production from Chalcopyrite for Supercapacitor Applications

Abstract: The primary purpose of this study was to produce an ore-based high-capacity supercapacitor electrode. For this, chalcopyrite ore was first leached with nitric acid, and then metal oxide synthesis was carried out immediately on nickel foam using a hydrothermal technique from the solution. Cauliflower-patterned CuFe2O4 with a wall thickness of about 23 nm was synthesized on the Ni foam surface, characterized by XRD, FTIR, XPS, SEM, and TEM investigations. The produced electrode also displayed a feature of a batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(54 reference statements)
2
3
0
Order By: Relevance
“…The non-linearity of this decrease is likely due to this phenomenon. Similar situations were observed in our previous studies as well [30,34,35]. At the same time, these results were obtained from the ZnO-modified Ni foam electrode.…”
Section: Electrochemical Propertiessupporting
confidence: 91%
See 3 more Smart Citations
“…The non-linearity of this decrease is likely due to this phenomenon. Similar situations were observed in our previous studies as well [30,34,35]. At the same time, these results were obtained from the ZnO-modified Ni foam electrode.…”
Section: Electrochemical Propertiessupporting
confidence: 91%
“…The intensity of the peaks is affected by the variables such as scan rate and ion adhesion to the electrode surface. Previous studies have shown that increasing scan rate results in higher peak intensities in a linear relationship [30,31,34]. This trend is confirmed by the slope values of 0.99544 in the anodic region and 0.9996 in the cathodic region, as depicted in the Randel-Sevcik plot shown in Figure 5c.…”
Section: Electrochemical Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…Supercapacitors (SCs) recognized as a promising sustainable energy storage device have attracted widespread attention, owing to their fast charge-discharge, high power, excellent long-term cycling life, etc. [1][2][3][4][5] Although the theoretical and experimental specific capacitances at relatively low sweep rates of activated carbons (ACs) are lower than those of metal oxides [6][7][8] and conductive polymers, 9,10 the electrochemical performances of the ACs at high charge-discharge rates are competitive. 11 Moreover, compared with metal oxides and conductive polymers, the superior conductivity, outstanding electrochemical stability, eco-friendliness and low cost also make ACs the most widely-used electrode materials of the commercial-level SCs.…”
Section: Introductionmentioning
confidence: 99%